Functionally graded concrete: Numerical design methods and experimental tests of mass‐optimized structural components. (February 2017) - Herrmann, Michael; Sobek, Werner
Abstract : Functional gradation of concrete elements makes it possible to align the internal composition of structural components with specific structural and thermal performance requirements. This alignment is made possible by continuously altering the characteristics of the material, including its porosity, strength, or rigidity, in up to 3 spatial dimensions. This principle can be applied to minimize the mass of the element and to create multifunctional properties. Numerical design methods are used to develop the gradation layout that serves as a digital blueprint for such components. This paper describes tests performed on functionally graded beams. These tests have made it possible to derive conclusions with respect to the elements' structural behavior. These tests also allow for a precise assessment of the weight savings that can potentially be achieved compared with structural components made from normal concrete. Test results were subsequently replicated by numerical simulations. The models calibrated in this step have established the basis to develop numerical design methods that rely on the principle of topology optimization.